Visual Perception of Object Motion during Self-Motion Does Not Depend on Heading Perception - Diederick C Niehorster; Li Li (i-Perception, 2012)
Recent studies have suggested that the visual system subtracts the optic flow pattern experienced during self-motion from the projected retinal motion of the environment to recover object motion, a phenomenon called “flow parsing”. In this experiment we tested whether the flow parsing process depends on heading perception, or only on the motion signals in optic flow. Two displays (83 × 83 deg, 500 ms) simulated an observer approaching a frontal plane that was composed of randomly placed dots or randomly placed dot pairs that formed a radial Glass pattern. The center of this radial Glass pattern was 10 deg away from the focus of expansion of the flow pattern. The radial Glass pattern allowed us to manipulate the perceived heading without affecting the motion input. For both displays, a probe dot moved upward on the frontal plane at 5 deg away from fixation. A horizontal component (along the world X -axis) under control of an adaptive staircase was added to the probe dot's vertical motion on the plane to determine when the probe motion was perceived as vertical. Heading perception was measured with a separate display containing the Glass pattern but no probe dot. We found that while the presence of the Glass pattern significantly biased the heading perception of eight participants, it did not affect the probe dot's perceived movement direction. We conclude that flow parsing is independent from heading perception and operates directly on the global motion information.